Indigenous Practice of Natural Resources Management at Pipal Dada, Palpa - Malla, U. M.; Chidi, Chhabi Lal (Himalayan Review, 2011)
Available with fulltext. Key words: Indigenous; Natural environment; Enroachment; Pipal Dada; Palpa The Himalayan Review Vol. 24-28 1993-1997 Page: 36-49 Uploaded date: 15 June, 2011